The Impact and Views of Communities on Underage Marriage in Ara Village, Bulukumba District - Muhammad Riyas Sabir; Andi Agustang (Jurnal Sosialisasi: Jurnal Hasil Pemikiran, Penelitian dan Pengembangan Keilmuan Sosiologi Pendidikan, 2023)
This study aims to find out how society views child marriage, the impact it causes, and the government's role in tackling underage marriage using qualitative methods with a descriptive approach. The results and conclusions of this study indicate that society views underage marriage as a natural thing based on hereditary habits. This underage marriage has several impacts, one of which is experiencing health problems. The government's role in tackling early marriage in Ara Village, Kec. Bonto Bahari Kab. Bulukumba is building a school in Ara Village, so married couples can still get an education